Frontal Sinus Fractures - Podolsky, Dale J.; Moe, Kris S. (Seminars in Plastic Surgery, 2021)
Management of frontal sinus fractures is controversial with no universally accepted treatment protocol. Goals of management are to correct aesthetic deformity, preserve sinus function when it is deemed salvageable, prevent sequela related to the injury, and minimize complications associated with intervention. Studies suggest that frontal sinus injuries, including disruption of the nasofrontal outflow tract (NFOT), can be managed nonoperatively in many cases. Advances in the utilization of endoscopic techniques have led to an evolution in management that reduces the need for open procedures, which have increased morbidity compared with endoscopic approaches. We employ a minimally disruptive protocol that treats the majority of fractures nonoperatively with serial clinical and radiographic examinations to assess for sinus aeration. Surgical intervention is reserved for the most severely displaced and comminuted posterior table fractures and unsalvageable NFOTs utilizing endoscopic approaches whenever possible.
Keywords: frontal sinus fractures; endoscopic; transorbital; navigation; cerebrospinal fluid